Cryopreservation of chayote (Sechium edule JACQ.SW.) zygotic embryos and shoot-tips from in vitroplantlets - Abdelnour-Esquivel, Ana; Engelmann, Florent (My University, 2002)
This paper presents the development of cryopreservation protocols for zygotic embryos and apices of chayote (Sechium edule Jacq. Sw.), a tropical plant species with recalcitrant seeds. Zygotic embryos of two cultivars, Ccocro negro (CN) and Claudio (Cl) could withstand cryopreservation, with survival percentages of 10 and 30 %, after desiccation to 23 and 19 % moisture content (fresh weight basis), respectively. Apices sampled on in vitro plantlets of cultivars Cl, 13 and JM were successfully cryopreserved using a vitrification technique. Optimal conditions included the culture of mother-plants for 22 days on medium containing 0.3 M sucrose, culture of excised apices on the same medium for 1 day, loading of apices for 20 min with 2M glycerol + 0.4M glycerol, treatment with a series of diluted PVS2 solution (60 % PVS2 followed by 80 % PVS2 solution for 15 min (cultivar Cocoro Blanco [CB]) or 30 min (cultivars CN and Cl) at each concentration), rapid freezing and thawing, washing of shoot-tips with a 1.2 M sucrose solution, followed by recovery on media with progressively decreasing sucrose concentrations until the standard concentration of 0.1 M was reached. The highest survival percentages achieved ranged between 17 and 38 %, depending on the cultivar
Keywords: Chayote; Sechium edule; Criopreservación; Embriones; Desecación; Sacarosa; In vitro; Cryopreservation; Embryos; Desiccation; Sucrose